Manganese incorporated on glucose as an efficient catalyst for the synthesis of adipic acid using molecular O2 in aqueous medium - Nale, S.D. (Applied Catalysis A: General, 2017)
A new manganese incorporated on glucose catalyst Mn@CC-SO3H-NH2 was synthesized and well characterized using FT-IR, PXRD, EDAX, SEM, TEM, [13] C cross-polarization NMR and BET analysis. The catalyst thus synthesized was studied for its utility in the synthesis of industrially important chemical adipic acid starting from readily available cyclohexanone using molecular O2 as a source. Adipic acid was obtained in maximum yield of 82% using Mn@CC-SO3H-NH2 catalyst in water as a solvent. The catalyst was easily recovered and reused for minimum five runs without any significant loss in the yield of products. Using molecular O2 as an oxidant and water as a solvent, the reaction is very important from green chemistry perspectives and can also be industrially feasible.
Keywords: Adipic Acid; Catalyst; manganese; recyclable; Water